Bayesian econometrics - Mauro Bernardi; Stefano Grassi; Francesco Ravazzolo (Journal of Risk and Financial Management, 2020)
The computational revolution in simulation techniques has shown to become a key ingredient in the field of Bayesian econometrics and opened new possibilities to study complex economic and financial phenomena. Applications include risk measurement, forecasting, assessment of policy effectiveness in macro, finance, marketing and monetary economics.
Keywords: 330; Bayesian econometrics; forecasting; macroeconomic and financial applications; MCMC methods